Down-Regulation of Cough during Exercise Is Less Frequent in Healthy Children than Adults. Role of the Development and/or Atopy? - Demoulin-Alexikova, Silvia; Marchal, François; Bonabel, Claude; Demoulin, Bruno; Foucaud, Laurent; Coutier-Marie, Laurianne; Schweitzer, Cyril E.; Ioan, Iulia (Frontiers in Physiology, 2017)
Cough is typically associated with physical activity in children with asthma, but the characteristics of the relationship between cough and exercise has not been established under physiological conditions. The aim of the study was to describe the effect of exercise on the reflex cough response elicited by a single breath of capsaicin in non-asthmatic children. A group of non-asthmatic adults was studied as reference. 30 children and 29 adults were recruited. The cough reflex sensitivity to capsaicin was first determined to establish the dose that provokes 5 cough efforts (C5). The number of coughs elicited by C5 (NC5) was then compared at baseline and during a standardized submaximal treadmill exercise. Data are expressed as median (interquartile range). Children and adults showed a significant decrease in NC5 (respectively from 5.0 (4.0 – 6.0) to 2.5 (2.0 – 4.0), p<0.0005 and from 6.0 (5.0 – 7.0) to 2.0 (0.0 – 3.0, p < 0.0005). During exercise, NC5 was observed to decrease in all adult subjects, but in only 24/30 children (80%, p=0.02). A trend for a higher incidence of personal and familial atopy was observed in children that lacked cough down-regulation during exercise compared with other children. It is concluded that the cough reflex response to capsaicin is down regulated by exercise in both children and adults. The effect however is less consistently observed in the former. The difference may reflect maturation of descending inhibitory pathways of the cough reflex, but may also be associated to atopy. The data stress the importance of assessing the time relationship of cough and exercise in questionnaire studies of asthma.